Violence on social networks - Dukic, Sandra (PONS - medicinski časopis, 2022)
The intent to humiliate, hurt or cause harm through the use of digital technology, that is through the use of smartphones and internet is called cyberbullying. Cyberbullying can take a number of different ways and forms. Most common ways of cyberbullying are blackmailing,  threats, harassment, sexual harasment, creating and using fake profiles impersonating the victim as well using their photos without permission. Within the program "Skola bez nasilja" (School without violence), in which 50 elementary (primary) schools participated, showed that 28% of students in Serbia have been involved in cyberbullying either as the victim or the bully, whilst 64% of the students stated that they have been a victim of cyberbullying in the last three months. A survey done by UNICEF showed that 1 in 3 young people have been a victim of cyber bullying. The survey was done across 30 different countires. The goal of the review paper is firstly to point out the importance of the protection of privacy and prevention of cyberbullying among minors, as well as the people that interact with kids and help in their educaton. To keep ourselves and our kids as safe as possible, it is necessary to inform all internet and social media users on how to protect their privacy and how to safely use digital devices in today’s age. Idea behind this work is to raise awareness among young people about the possible dangers of social media which could lead to negative consequences such as anxiety, depression, isolation, suicidal thoughts and even suicide. Key words: violence, social media, cyberbullying, internet, safety, kids
Keywords: Key words: violence, social media, cyberbullying, internet, safety, kids